Floorball goaltending movements during a game: A quantitative observational study - Eva Tengman; Alexandra Pettersson; Linnea Jönsson; Taru Tervo (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background More knowledge about floorball goalkeepers’ game movements and biomechanical demands is warranted. Therefore, the aim of this study was to observe type and frequency of female floorball goalkeepers’ movements during a game. Methods Twelve female goalkeepers (mean age 22 years) were included. An observational study design using video recording was used to explore goalkeepers’ movements during a game. Three different positions were reported in minutes, percent of playing time, and the number of times the goalkeepers performed different movements. Results The results revealed that of total playing time, goalkeepers were playing on their knees 31% (± 10%) of the time, in quadruped position 1.3% (± 1.9%) and 67% (± 11%) they played standing. Five movements were performed more frequently; short side movements, pull, stand up, small rotation with legs, and longer ball covers at the goalpost. A large variation in movement was seen regarding how many and what type of movements each goalkeeper performed during the game. Conclusion Floorball goalkeepers perform a high number of movements and spend a substantial amount of the match time on their knees. There is no existing research on how these game aspects may impact load as well as physical needs, emphasizing the need for further research. Knowledge from the study lays the groundwork for further studies and may be used when developing future preventive training programme and rehabilitation.